THE MASS MEDIA AND AFRICAN ELECTIONS - Amadi, Fred A. (European Scientific Journal, ESJ, 2013)
Using Nigeria as a setting, this paper examines how media’s reportorial mistakes impact African electoral processes. Eight newspaper textual exemplars were theoretically sampled and presented in a titled Text Box. The texts were subjected to analysis by means of the analytical resources that brim in Critical Discourse Analysis (CDA). Discussion drew on reactions from the reporters who wrote the analysed textual exemplars. Discussion also drew on comments about the 2013 Zimbabwe elections. Results are that questionable communication models tease African media into inaccuracies; and such inaccuracies are found as conniving at electoral abuses in Africa. Conclusion is that until the media snap out of their debilitating ineptitude, electoral outcomes in Africa will continue to be out of synch with the will of the electorates